Distribution, toxicity, interactive effects, and detection of ochratoxin and deoxynivalenol in food: A review. (1st June 2022) - Ganesan, Abirami Ramu; Mohan, Kannan; Karthick Rajan, Durairaj; Pillay, Arti A.; Palanisami, Thavamani; Sathishkumar, Palanivel; Conterno, Lorenza
Graphical abstract: Highlights: Mycotoxins OTA and DON are widely distributed in agro-products. The distribution of OTA and DON prevalent in the colder and temperate region. The interaction of OTA/DON with co-existing chemicals pose a serious health issue. The detection method of OTA/DON with other toxins in food matrix was evaluated. The mitigation strategy through biocontrol and detoxification were highlighted. Abstract: Mycotoxins are secondary metabolites of fungi that cause severe damage to agricultural products and food in the food supply chain. These detrimental pollutants have been directly linked with poor socioeconomic patterns and human health issues. Among the natural micropollutants, ochratoxin A (OTA) and deoxynivalenol (DON) are widely distributed in food materials. The primary occurrence of these mycotoxins is reported in almost all cereal grains and fresh agro-products. Both mycotoxins have shown harmful effects, such as nephrotoxic, hepatotoxic, and genotoxic effects, in humans due to their complex structural formation during the degradation/acetylation reaction. In addition, improper preharvest, harvest, and postharvest handling tend to lead to the formation of OTA and DON in various food commodities, which allows different harmful fungicides in practice. Therefore, this review provides more insight into the distribution and toxicity of OTA/DON in the food matrix and human health. Furthermore, the interactive effects of OTA/DON with co-contaminated organic and inorganic compounds are discussed. Finally, international regulation and mitigation strategies for detoxication are critically evaluated to meet food safety and good agriculture practices.